2009
DOI: 10.1515/znc-2009-3-420
|View full text |Cite
|
Sign up to set email alerts
|

New Pyridine Alkaloids from Rove Beetles of the Genus Stenus (Coleoptera: Staphylinidae)

Abstract: Three new pyridine alkaloids were detected in the pygidial glands of some Stenus species. The chemotaxonomic signifi cance of the occurrence of these alkaloids and stenusine in different Stenus species is discussed. The antimicrobial properties of (Z)-and (E)-3-(2-methyl-1-butenyl)-pyridine and the deterrent activities of stenusine and norstenusine were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[1] We found that their secretions were composed mainly of the pyridine alkaloids (Z)-and (E)-2 [7] and the so far unknown compound 3. [1] We found that their secretions were composed mainly of the pyridine alkaloids (Z)-and (E)-2 [7] and the so far unknown compound 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] We found that their secretions were composed mainly of the pyridine alkaloids (Z)-and (E)-2 [7] and the so far unknown compound 3. [1] We found that their secretions were composed mainly of the pyridine alkaloids (Z)-and (E)-2 [7] and the so far unknown compound 3.…”
Section: Resultsmentioning
confidence: 99%
“…[3] If the fluid is constantly released, the Stenus beetles can travel distances up to 15 m with velocities of 40-75 cm/ s by this method, also called skimming. [5] Furthermore, 1 exhibits antimicrobial properties [6] and deterrent [7] activities against predators. [3] For some Stenus species, we found a characteristic fingerprint of 1 in terms of its stereochemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…(Z)-3-(2-Methyl-1-butenyl)pyridine (2) shows higher antimicrobial activity than stenusine (1). 3 Furthermore alkaloid 2 occurs among others in that fraction of Stenus species that are missing lateral tergite borders on all segments of the abdomen, a character that can be definitely classified as phylogenetically advanced. 5 In this way the formation of 2 in addition to 1 might have been an important step in the evolution of the pygidial gland secretion in the genus Stenus.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…4,5 It is also remarkable that 2 shows a higher antimicrobial activity than 1. 3 The biosynthesis of stenusine (1) in S. bimaculatus Gyllenhal has previously been investigated. L-Lysine forms the piperidine ring, L-isoleucine the side chain, and acetate the N-ethyl group.…”
mentioning
confidence: 99%
“…We tested the hypothesis that Stenus beetles impregnate the surface of their body with the pygidial gland secretion to defend themselves against microorganisms and found that the isomeric mixture of synthetic stenusine, similar to that of S. comma and (±)‐norstenusine,10 in concentrations occurring in nature, significantly inhibits the growth of bacteria ( Serratia entomophila ) and fungi ( Beauveria bassiana ) 11. A second function for this secretion, and thus of stenusine ( 1 ) and norstenusine ( 21 ), is that it acts as a deterrent against predators like Leptothorax platythorax ants, and this could be proven by feeding experiments 12. To test the biological activity of the individual stenusine and norstenusine isomers, we are interested in a straightforward synthetic route leading to all stereoisomers.…”
Section: Introductionmentioning
confidence: 99%